Impulse Buying Behaviors and Customer Trust During Twin Date Online Promotion: Using Prisma Method with Systematic Literature Review - Fismayatni Cholifah; Achmad Husen; suparno suparno (Dinasti Publisher, 2025)
This study aims to analyze the impact and relationship between impulse buying behaviors, customer trust, twin date online promotion, and promotion event in the marketing sector. Base on PRISMA method as a guideline with technical a systematic literature review, this study analyzed 20 scholarly articles published between 2018 and 2024 from various countries, focusing on the marketing segmentation with categories impulse buying behaviors, customer trust, and promotion event in e-commers marketing digital. To ensure the quality of the included studies, only articles indexes in Scopus Q1, Q2, Q3, and Q4 were considered using the Watase UAKE system. The objective of this study is to provide a comprehensive understanding of the context and theoretical foundations employed in these studies. Regarding theoretical foundations, Theory of Planned Behavior and Elaboration Likelihood Model used in marketing to understand and influence customer behavior. The finding of this study is expected to contribute to the development of more effective policies for enhancing the impulse buying behaviors and customer trust during twin date online promotion. The results of the study show that promotion event marketing such as during twin date online promotion plays a significant role in impulse buying behavior. This impact and relationship ultimately have a positive environment on buying behavior. This writing uses Google Scholar and Scopus as an in-depth literature review and trusted academic sources.